2012
DOI: 10.1098/rspb.2012.0246
|View full text |Cite
|
Sign up to set email alerts
|

A model of sexual selection and female use of refuge in a coercive mating system

Abstract: In many non-monogamous systems, males invest less in progeny than do females. This leaves males with higher potential rates of reproduction, and a likelihood of sexual conflict, including, in some systems, coercive matings. If coercive matings are costly, the best female strategy may be to avoid male interaction. We present a model that demonstrates female movement in response to male harassment as a mechanism to lower the costs associated with male coercion, and the effect that female movement has on selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In summary, we showed that the Bokides et al [1] model only exhibits equilibrium behavior. We also proved that any existing equilibrium strategy would be globally asymptotically stable, improving on their results.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…In summary, we showed that the Bokides et al [1] model only exhibits equilibrium behavior. We also proved that any existing equilibrium strategy would be globally asymptotically stable, improving on their results.…”
Section: Discussionmentioning
confidence: 49%
“…For the reader's convenience, we briefly review and summarize main results of the Bokides et al model [1]. The model is styled similar to classical habitat choice games [13] with a fixed population of females (N f ) and males (N m ) vying to maximize resource intake and mating benefits.…”
Section: A Coercive Mating Gamementioning
confidence: 99%
See 3 more Smart Citations